Smart graphene-based hydrogel promotes recruitment and neural-like differentiation of bone marrow derived mesenchymal stem cells in rat skin. (26th January 2021) - Zhang, Chenzhen; Yuan, Tie-Jun; Tan, Min-Hong; Xu, Xue-Han; Huang, Yan-Fen; Peng, Li-Hua
Abstract : Strategies to direct the differentiation of endogenous bone marrow derived mesenchymal stem cells (BMSCs) in vivo following recruitment to the injured site are critical to realizing the potential of stem cell-based therapies. Abstract : Strategies to direct the differentiation of endogenous bone marrow derived mesenchymal stem cells (BMSCs) in vivo following recruitment to the injured site are critical to realizing the potential of stem cell-based therapies. But the differentiation efficiency of BMSCs remains limited without direction. Here we demonstrated a novel strategy to promote neuronal differentiation of BMSCs using cross-linked polyethylenimine (PEI) grafted graphene oxide (GO) as the enzyme responsive vector for delivering active genes to BMSCs. In vivo, a core–shell microfiber arrayed hydrogel with a chemokine (SDF-1α) and the cross-linked GO-PEI/pDNAs-bFGF microparticles incorporated into the shell and core, respectively, were constructed. The arrayed hydrogel was shown to recruit and stimulate the neural-like differentiation of BMSCs effectively by delivering the CXCL12 and GO-PEI/pDNAs-bFGF in a self-controlled manner. With this strategy, both in vitro and in vivo neuronal differentiation of BMSCs with function were accelerated significantly. The cross-linked GO-PEI mediated gene transfection together with a multi-functional microfiber arrayed hydrogel provide a translatable approach for endogenous stem cell-based regenerative therapy.